Kanban systems - Bollinger, Steven R.; Sieverding, Keith (Manufacturing insights)
Kanban is a Japanese term for a visual system used to trigger activity upstream in a given process. The most important point to remember about a Kanban system is that the best Kanban system is none at all and it is only a substitute for not being able to implement single-piece flow in your process.